LAND ACQUISITION AND RIGHT TO FAIR COMPENSATION - Tiwari, Pramod; Prabhat Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This article discusses the new law and an attempt to achieve fairness in the payment of compensation. In India, price is the most important issue in the majority of land acquisition disputes. It is necessary to get the right information about the price of land. Secrecy, misinformation, and misconception are as common in land-related sales and purchases as in arrange marriages. There are different ranges of prices that vary per acre of the land. The highest point of the price of land is in an urban area, especially in metro cities. For paying compensation it is necessary to have a market and it is very difficult to fix the price of that kind of land for which the market does not exist. Some regions of the country have few land sales and purchase every year especially in the area of Adivasi lands that are protected from sales to an outsider. How can the price be fixed by the acquiring authority in the Adivasi area? Such types of objection are still very much prevalent and which has not been able to be solved because of genuine issues.